A pharmacovigilance study to determine risk of mortality in male and female patients with Alzheimer's disease using Rivastigmine - Shehab, Habibul Mohsin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.